Molecular allergen sensitization profile and casein threshold determination predicting the persistence of cow's milk protein allergy in Tunisia (North Africa) - Ouerdani, Yasmina; Zamali, Imen; Galai, Yousr; Ben Hmid, Ahlem; Nasri, Yosra; Ben Sghaier, Ines; Kebaier, Hayet; Louzir, Hechmi; Bouguila, Jihene; Ben Alaya Bouafif, Nissaf; Ben Ahmed, Mélika; Samoud, Samar (Frontiers in Allergy, 2025)
BackgroundCow's milk protein allergy (CMPA) represents a major health concern in Tunisia, with diagnostic challenges influencing disease prognosis. Molecular allergen testing has emerged as a valuable tool to enhance diagnostic accuracy and predict disease persistence.ObjectiveThis study aims to characterize the clinical and epidemiological features of CMPA in a Tunisian population, with a particular focus on the role of molecular allergens in assessing disease chronicity.MethodsA retrospective analysis was conducted on 262 cases of IgE-mediated CMPA diagnosed at the Pasteur Institute of Tunis between 2020 and 2023. Sensitization to molecular allergens was assessed using ImmunoCAP (Phadia 100).ResultsCMPA symptoms predominantly manifested in infancy (94%, 246/262), with a male predominance (sex ratio: 1.6). Acute reactions were the most frequent presentation (69.9%, 79/113), and polysensitization was common (81%, 212/262), particularly to β-lactoglobulin. Spontaneous resolution occurred in approximately 33% of cases (29/87), with a mean age of 3 years and 8 months. Persistent CMPA was significantly associated with elevated IgE levels to whole milk, β-lactoglobulin, and casein (p < 0.05). ROC curve analysis identified predictive thresholds for disease persistence, including 4.2 kU/L for whole milk-specific IgE and 0.37 kU/L for casein-specific IgE (p = 0.006).ConclusionMolecular allergen testing improves CMPA diagnosis and offers critical prognostic insights. The identification of IgE thresholds may facilitate early risk stratification and guide personalized management strategies.